The role of product presentation factors in product evaluation and online food delivery partners - Ardiansyahmiraja, Bobby; Nadlifatin, Reny (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Online Food Delivery Services (OFDS) platforms are growing rapidly in Indonesia. However, when compared to neighboring countries such as Malaysia, OFDS user penetration in Indonesia is still very minimal despite the high level of user consumption. The level of user penetration is directly related to customer retention, where product presentation is an important part of customer retention. Previous studies focusing on product presentation factors are still rare. The product presentation factors studied in this research include the combination of product color and background, social presence, and calorie information. These three factors can be directly managed by restaurant partners and have been proven to be important in previous studies related to their relationship with product evaluation. This study uses an experimental design and Structural Evaluation Modeling (SEM) approach. A total of 240 respondents participated in this study. Of the eight hypotheses, four were accepted. Social presence and calorie information were found to significantly affect product attitude negatively. In addition, product attitude (β = 0.733, p = 0.001) and brand trust (β = 0.338, p = 0.001) had a significant positive effect on purchase intention. The discussion and managerial implications are further discussed in this study.